Peningkatan Kapasitas dan Keberlanjutan UMKM Pedesaan Melalui Edukasi Perlindungan Hukum, Literasi Keuangan Digital, dan Pemasaran Produk: Studi Kasus Desa Paku, Bangka Selatan (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to improve the capacity and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Paku Village, Payung District, South Bangka, through an integrated intervention approach. The program's primary focus is education on legal protection, digital financial literacy, and product marketing, which can strengthen the competitiveness of rural MSMEs. Rural MSMEs often face various challenges, such as difficulties in complying with legal regulations, limited access to financing, and limited market reach, which hinder their growth. Therefore, this program adopts a participatory approach involving workshops, training, and direct mentoring to provide MSMEs with the knowledge and skills necessary to overcome these challenges. Expected outcomes of this program include increased understanding of business legality, adoption of digital financial transactions, and the implementation of effective digital marketing strategies. Through the integration of these three aspects, this program aims to increase MSME income, expand their competitiveness, and create new jobs at the local level. With long-term impacts that include village economic development and community empowerment, this program is expected to become a sustainable model for MSMEs in other villages in the area.